Efektivitas intervensi non-farmakologi terhadap penurunan tekanan darah pada lansia dengan hipertensi: A systematic review - Inaya Safitri Puryanti; Iwan Ardian; Iskim Luthfa; Wahyu Endang Setyawati (Holistik Jurnal Kesehatan, 2026)
Background: Hypertension in the elderly is a significant health concern because it can lead to serious cardiovascular complications. Although antihypertensive medications are effective, long-term use often leads to side effects and the risk of polypharmacy. Therefore, non-pharmacological interventions are an option worth considering as supportive therapy. Various methods, such as progressive muscle relaxation, exercise for the elderly, and dietary adjustments, have been extensively studied to help lower blood pressure in the elderly. Purpose: To examine the effectiveness of non-pharmacological interventions in lowering systolic and diastolic blood pressure in the elderly with hypertension. Method: This study used a systematic review design following PRISMA guidelines. A literature search was conducted in PubMed, Google Scholar, and ScienceDirect for articles published between 2020 and 2026. Inclusion criteria included randomized controlled trials and quasi-experimental studies with participants aged 60 years and older. A total of 14 articles meeting the criteria were analyzed descriptively to determine the effects of the interventions on blood pressure. Results: Progressive muscle relaxation, exercise for the elderly, and the DASH diet have positive effects on lowering blood pressure. The average reduction achieved was 10–15 mmHg for systolic blood pressure and 5–10 mmHg for diastolic blood pressure after the intervention. These findings confirm that non-pharmacological approaches play a crucial role in supporting the management of hypertension in the elderly. Conclusion: Non-pharmacological interventions have been shown to be effective in helping lower blood pressure in the elderly with hypertension. The implementation of this approach needs to be strengthened in community nursing and eldercare services as a safer, more holistic, and sustainable hypertension management strategy.   Keywords: Blood Pressure; Elderly; Hypertension; Non-Pharmacological Interventions.